1981
DOI: 10.1288/00005537-198109000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Homograft septal cartilage for attic support in intact canal wall tympanomastoidectomy and tympanoplasty

Abstract: The postoperative formation of attic retraction pockets following tympanoplasty, with or without mastoidectomy, has often been a significant cause of recurrent disease accompanied by decreased hearing levels. Nasal septal cartilage is recommended as a successful homograft material for attic support. The basis and indications for its use are discussed. Preparation and storage of the homograft materials and surgical technique are described. Long‐term results are reported, including a special group in which the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Sources of cartilage include ear tragus, knee meniscus, rib cartilage, and nasal septum. 4–9 Cartilage has demonstrated good results in tympanic membrane reconstruction but has the reputation of sacrificing maximum hearing improvement, because of “loading” of the middle ear mechanism with increased mass and stiffness. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Sources of cartilage include ear tragus, knee meniscus, rib cartilage, and nasal septum. 4–9 Cartilage has demonstrated good results in tympanic membrane reconstruction but has the reputation of sacrificing maximum hearing improvement, because of “loading” of the middle ear mechanism with increased mass and stiffness. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Basic materials have included autografts, homografts, and heterografts of soft tissue, cartilage, and bone. [1][2][3][4][5][6][7][8][9] Synthetic materials have also been used successfully to repair the osseous canal wall. 10 -13 The desirability of using autologous tissues for repair, especially in chronic otitis media, led me to begin using autologous bone in the form of mortar or pate for this purpose in 1973.…”
mentioning
confidence: 99%
“…Pappas et al [33] used homograft nasal septal cartilage for attic support with a success rate of 84%. Kinney [34] reported that the number of recurrences are reduced with attic obliteration by cartilage and perichondrium.…”
Section: Discussionmentioning
confidence: 99%